Effect of the mycotoxin aflatoxin B1 on a semi-continuous anaerobic digestion process. (August 2018) - Tacconi, Chiara; Cucina, Mirko; Pezzolla, Daniela; Zadra, Claudia; Gigliotti, Giovanni
Highlights: Aflatoxin B1 (AFB1) contamination is an emerging issue for feed and food production. Biomethane can be recovered from AFB1 contaminated corn through anaerobic digestion. Semi-continuous digestion was affected at AFB1 concentration higher than 25 µg kg −1. When an AFB1 concentration of 100 µg kg −1 was tested, the process was inhibited. In the semi-continuous process there was a progressive accumulation of AFB1. Abstract: Cereals are primary crops and are the most important raw material for feed and food production. Increasing aflatoxin B1 (AFB1) contamination of corn is an emerging issue, and disposal procedures for AFB1-contaminated corn are not currently defined. Recovery of contaminated corn through anaerobic digestion may represent a suitable strategy for its valorisation; however, only a few studies concerning the effect of AFB1 on anaerobic processes can be found. Thus, the purpose of the present work was to evaluate the effect of the mycotoxin AFB1 on a semi-continuous anaerobic digestion (AD) process. Semi-continuous trials were carried out, and the biomethane production from ABF1-contaminated feedstocks (25, 50, and 100 µg kg −1 AFB1 wet weight) was compared to that from non-contaminated feedstock. Moreover, the feasibility of the agronomic re-use of the digestate, and the fate of AFB1 during AD was assessed. No adverse effect of 25 µg kg −1 AFB1 contamination of feedstock on biomethane yield was observed. In contrast, 100 µg kg −1 AFB1 in the feedstock resulted in inhibition of the process due to the accumulation of organic acids, and to the decrease of the pH in the digestate (from 8.1 to 5.4). The continuous addition of AFB1-contaminated feedstock led to accumulation of the mycotoxin in the digestates. Consequently, a composting process should always precede the agricultural re-use of digestates in order to remove AFB1 and the residual phytotoxicity.